Multimode Inverter Control Strategy for LVRT and HVRT Capability Enhancement in Grid Connected Solar PV System - C. Nithya; J. Preetha Roselyn (IEEE Access, 2022)
Grid Connected Photo Voltaic (GCPV) system should be susceptible to grid faults and load curtailment without disconnection and supports in grid stability. During grid faults, there is an increase in dc link voltage, dip in grid voltage which leads to over-current on the grid side. Similarly, when demand is suddenly removed, the voltage at the PCC rises above its nominal value. This leads to possible damage in the PV inverters and hence need to disconnection of GCPV system leading to islanding scenarios. Hence, the GCPV system need to be equipped with Fault Ride Through (FRT) capability to address the issues related to low voltage and high voltage conditions in the grid side. In this work, multimode inverter control strategy is proposed with FRT capability according to grid code compliance. An improved current control technique is proposed as FRT based protection strategy during grid faults and sudden removal of load. According to severity of faults, a fault level detection is developed which triggers the control strategies to generate the reference real and reactive power with respect to the grid code compliance. The performance analysis of the proposed FRT control strategy is implemented in 100 kW two-stage GCPV system in MATLAB/Simulink 2018b environment and tested under low voltage and high voltage ride through conditions. The proposed control strategy is implemented in hardware setup of 1 kW GCPV system. The experimental results prove the effectiveness of the proposed inverter FRT based control strategy in enhancing the system parameters during system disturbances under different modes of operation.